Pengaruh Kompleksitas Tugas, Tekanan Anggaran Waktu Dan Pengalaman Auditor Terhadap Kualitas Audit - Ariestanti, Ni Luh Dwi; Latrini, Made Yenni (E-Jurnal Akuntansi, 2019)
At this time competition between companies is increasing accompanied by various problems faced by companies in Indonesia. In dealing with this problem, the company managers need accountant services, especially public accounting services. Audit quality is one of the important things in approaching the existence of a company. This study aims to prove empirically the effect of task complexity, time budget pressure and auditor experience on audit quality. This research is associative quantitative research. The data used in this study is primary data obtained by distributing questionnaires to each auditor at 9 Public Accounting Firms (KAP) in Province of Bali. The analysis technique used in this study is multiple linear analysis. The test results aimed at task complexity have a negative and significant effect on audit quality. Time budget pressure has a positive and significant effect on audit quality. The auditor's experience has a positive and significant effect on audit quality. Keywords: Task complexity, time budget pressure, auditor experience, audit quality